21.2: Highly Reliable Oxide Thin Film Transistor with Novel Oxide Passivation Layers By All‐Printing Processes. Issue 1 (June 2015) - Matsumoto, Shinji; Saotome, Ryoichi; Hirano, Yukiko; Sone, Yuji; Arae, Sadanori; Kusayanagi, Minehide; Nakamura, Yuki; Ueda, Naoyuki; Yamada, Katsuyuki
Abstract : We have developed highly reliable oxide TFT arrays by allprinted maskless process from gate to passivation layers with 100 ppi RGB resolution. The threshold voltage shifts under positive and negative bias‐temperature‐stress at 50 °C after 10 5 seconds were less than 0.8 and 0.3 V, respectively.